2021
DOI: 10.1002/edn3.274
|View full text |Cite
|
Sign up to set email alerts
|

Assessing environmental DNA metabarcoding and camera trap surveys as complementary tools for biomonitoring of remote desert water bodies

Abstract: Biodiversity assessments are indispensable tools for planning and monitoring conservation strategies. Camera traps (CT) are widely used to monitor wildlife and have proven their usefulness. Environmental DNA (eDNA)‐based approaches are increasingly implemented for biomonitoring, combining sensitivity, high taxonomic coverage and resolution, non‐invasiveness and easiness of sampling, but remain challenging for terrestrial fauna. However, in remote desert areas where scattered water bodies attract terrestrial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 134 publications
1
10
0
Order By: Relevance
“…Using eDNA from soil, sediment, water, or air sample inventories, we can complement existing species monitoring efforts through the identification of thousands of species at once, including plants, animals, and microbes (Stat et al 2019;Lin et al 2021;Nørgaard et al 2021). Use of eDNA can greatly complement traditional species monitoring by enabling greater taxonomic resolution (Deiner et al 2017;Ruppert et al 2019), the detection of species which tend to avoid the presence of humans (Yonezawa et al 2020;Mas-Carrió et al 2021), or organisms such as bacteria and fungi which can be difficult to monitor using traditional observations (Frøslev et al 2019;Liddicoat et al 2022). Comparisons of eDNA with observational methods have also indicated their potential to help capture additional elements of ecologically relevant information, such as the functional diversity of various groups of species (Aglieri et al, 2021;Donald et al 2021;Sigsgaard et al 2021), particularly with regards to identifying ecological indicators (Yan et al 2018;Blattner et al 2021;Seymour et al 2021).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Using eDNA from soil, sediment, water, or air sample inventories, we can complement existing species monitoring efforts through the identification of thousands of species at once, including plants, animals, and microbes (Stat et al 2019;Lin et al 2021;Nørgaard et al 2021). Use of eDNA can greatly complement traditional species monitoring by enabling greater taxonomic resolution (Deiner et al 2017;Ruppert et al 2019), the detection of species which tend to avoid the presence of humans (Yonezawa et al 2020;Mas-Carrió et al 2021), or organisms such as bacteria and fungi which can be difficult to monitor using traditional observations (Frøslev et al 2019;Liddicoat et al 2022). Comparisons of eDNA with observational methods have also indicated their potential to help capture additional elements of ecologically relevant information, such as the functional diversity of various groups of species (Aglieri et al, 2021;Donald et al 2021;Sigsgaard et al 2021), particularly with regards to identifying ecological indicators (Yan et al 2018;Blattner et al 2021;Seymour et al 2021).…”
Section: Future Prospectsmentioning
confidence: 99%
“…eDNA methods for detecting terrestrial reptiles are not limited to soil and sediment samples. Several recent studies have shown the potential of using water samples to detect terrestrial mammals (Harper, Griffiths, et al, 2019 ; Lyet et al, 2021 ; Mas‐Carrió et al, 2021 ; Mena et al, 2021 ), and birds (Mas‐Carrió et al, 2021 ). Terrestrial animals visit water bodies, and their DNA can be transferred to aquatic systems directly through behaviors such as foraging, drinking, swimming, defecation, and bathing, or indirectly via rain and soil drainage (Coutant et al, 2021 ).…”
Section: Aquatic Vs Terrestrial Reptilesmentioning
confidence: 99%
“…Terrestrial animals visit water bodies, and their DNA can be transferred to aquatic systems directly through behaviors such as foraging, drinking, swimming, defecation, and bathing, or indirectly via rain and soil drainage (Coutant et al, 2021 ). Mas‐Carrió et al ( 2021 ) used the 12S primer VERT01 (Taberlet et al, 2018 ) to target terrestrial birds, reptiles, and mammals in remote desert water bodies, although they did not detect any reptiles through eDNA or through camera trap surveys.…”
Section: Aquatic Vs Terrestrial Reptilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, metabarcoding analysis of eDNA from stream water (Lyet et al, 2021) and terrestrial sediments (Leempoel et al, 2020) combined with CTs has been found to be efficient for monitoring terrestrial mammals. The number of such vertebrate studies combining water eDNA and CTs is growing rapidly, in covering all sorts of habitats from reefs (Stat et al, 2018; Boussarie et al, 2018) to ponds (Mas-Carrió et al, 2022; Harper et al, 2019).…”
Section: Introductionmentioning
confidence: 99%